2002
DOI: 10.1042/bj20020586
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of phospholipases D1 and D2 in sphingosine 1-phosphate-induced ERK (extracellular-signal-regulated kinase) activation and interleukin-8 secretion in human bronchial epithelial cells

Abstract: Sphingosine 1-phosphate (S1P), a metabolite of sphingomyelin degradation, stimulates interleukin-8 (IL-8) secretion in human bronchial epithelial (Beas-2B) cells. The molecular mechanisms regulating S1P-mediated IL-8 secretion are yet to be completely defined. Here we provide evidence that activation of phospholipases D1 and D2 (PLD1 and PLD2) by S1P regulates the phosphorylation of extracellular-signal-regulated kinase (ERK) and IL-8 secretion in Beas-2B cells. S1P, in a time- and dose-dependent manner, enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 56 publications
(70 reference statements)
3
57
0
Order By: Relevance
“…BEAS-2B cells maintain the characteristics of primary bronchial epithelial cells including expression of ICAM-1, eotaxin and CXCL8 [19][20][21], while KU812 cells constitute the phenotypes of basophils, such as histamine release and FcgammaRII expression [22]. We also used primary bronchial epithelial cells and peripheral blood basophils to confirm our findings of BEAS-2B and KU812 cells.…”
Section: Discussionsupporting
confidence: 68%
“…BEAS-2B cells maintain the characteristics of primary bronchial epithelial cells including expression of ICAM-1, eotaxin and CXCL8 [19][20][21], while KU812 cells constitute the phenotypes of basophils, such as histamine release and FcgammaRII expression [22]. We also used primary bronchial epithelial cells and peripheral blood basophils to confirm our findings of BEAS-2B and KU812 cells.…”
Section: Discussionsupporting
confidence: 68%
“…Npr3 (natriuretic peptide receptor-3) has previously been shown to be rapidly down-regulated after birth and is proposed to maintain the fetal lung in a fluid-filled state (32). Pld1 is a phosphatidylcholine-specific phospholipase expressed in the lung (33,34) that may be involved in surfactant metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In dataset L1, the time points can be represented as the vector (E14, E17, E19, P7, P14, P28), which is correlated with (0, 3,5,12,19,33). The time-to-birth profile is Abs((0, 3, 5, 12, 19, 33) -5.5) 5 (5.5, 2.5, 0.5, 6.5, 13.5, 27.5).…”
Section: Time/stage Of Lung Development and Time-to-birth Profiles Fomentioning
confidence: 99%
“…HBEpCs-Previous studies have demonstrated stimulation of mitogenic signaling pathways for S1P, LPA, and growth factors in human airway smooth muscle and epithelial cells (1,21,34,35). To examine ERK activation further, HBEpCs were challenged with 1 M LPA or 20 ng/ml PDGF-BB, and phosphorylation of ERK was analyzed by Western blotting with phospho-specific antibodies against threonine/ tyrosine residues.…”
Section: Lpa-induced Erk1/2 Activation Is Sensitive To Ag 1296 and Ptmentioning
confidence: 99%